Perubahan Sosial dan Ekonomi Masyarakat Pasca Pembangunan Institut Teknologi Sumatera (Studi Kasus Desa Way Huwi Kecamatan Jati Agung Lampung Selatan) - Efendi, Nadila Putri; Hendarso, Yoyok; Yulasteriyani; Decka Pratama Putra (Master Program in Sociology, Faculty of Social and Political Sciences, Universitas Sriwijay, 2024)
This study discusses the socio-economic changes in the community in Way Huwi Village after the Sumatra Institute of Technology (ITERA) construction. The study used a descriptive qualitative method with a case study approach. Data were collected through observation, in-depth interviews, and documentation. The results show that before the construction of ITERA, the people of Way Huwi Village still upheld cooperation and solidarity. However, after the construction of the campus, there was a change that led to a more individualistic tendency. Economically, the village community began to take advantage of the campus by diversifying jobs, thus creating new business opportunities, especially in the trade sector, which increased the local community's income. Likewise, the community's mindset changed, mainly focusing on income, education, and morals. However, negative impacts emerged, such as increased crime, juvenile delinquency, and violations of the social value system and norms.